Implementation of the Arabic Language Achievement Development Program - Fatma, Okita; Jailani, Muhammad; Arifah, Zakiyah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
The Arabic Language Achievement Development Program has a strategic role in improving students' Arabic language skills, especially in the context of educational institutions that focus on developing language skills. This study aims to examine the implementation of the actuating function in the Arabic language achievement development program at MA Shirothul Fuqoha'. The research method used is a qualitative descriptive approach. The results of the study indicate that the actuating function in the Arabic language achievement development program at MA Shirothul Fuqoha' has been carried out well, in accordance with George R. Terry's theory. This program is one of the efforts to improve the quality of foreign languages ​​in the institution. The implementation of this program provides a real contribution as an innovative solution in overcoming the challenges of Arabic language mastery among students.‎